Analisis Buku Ajar Akidah Akhlak Madrasah Ibtidaiyah - Ni’mah Afifah (Universitas Alma Ata, 2013)
Textbooks as one of the learning tools play an important role to improve the quality of learning that is carried out by a teacher. Textbooks can affect the reader either teachers or students in all aspects, i.e thinking, attitudes and behavior. Writers on this occasion would explain the quality of textbooks on the subjects of faith and morality particulary at primary school in Grade 4, 5 and 6. Analyzed book begins from standards of competence and basic competence, purpose, material in the book as well as an image or chart in that book. Next, the analysis is done by comparing the standards of competence and basic competence with the material displayed in the book which consists of images, making the proposition, multicultural and gender mainstering.Keyword; textbook learning, moral and faith learning